A transitivity analysis of the final 2020 presidential debate Donald Trump and Joe Biden - Halim, Nurhaliza; Megah, Suswanto Ismadi (Universitas Riau Kepulauan, 2023)
This study is aimed to determine the ideological content implied in the debate speeches of Donald Trump and Joe Biden by using the transitivity theory of Halliday. The method used is descriptive qualitative. From the data found, the highest frequency of process types is found in Donald Trump with a total of 63 (100%), while Joe Biden with 32 times (51%). From this study, it can be concluded that the Transitivity analysis that most often occurs in the Donald Trump and Joe Biden debate is the Material Process. This process is the process of doing something. In this case, Donald Trump and Joe Biden took action in dealing with coronavirus cases in America. Donald Trump and Joe Biden's ideological stance is to show that he cares about the coronavirus cases in America. This is done bay both candidates due to show how they have struggled to handle the pandemic very well in order to get sympathy from ten audiences.